Comparative Analysis of Snail Growth using Different Local Feeds - S, Mamman G.; R, Umaru (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2024)
This study aimed at comparing growth performance, establishing different locally available feeds and determine the most efficient among the feedstuff for snail using four different feeds (Moringa oleifera leaves, Carica papaya leaves, Citrillus lanatus peels and broiler starter mash for 16 weeks at the Forest Institute of Nigeria (FRIN). Forty (40) Archachatina marginata (African Snail) of 8 weeks were used for the study. The snails were randomly divided into groups of 10 snails each. The groups were randomly assigned to 3 local diets and a concentrate (manufactured feed) in a Completely Randomized Design (CRD). The snails were housed in motor tyres and each was half filled with hot water-treated loamy soil 5cm depth .The soil was moistened two times daily by sprinkling of tap water. Pits were made round the tyres, filled with water mixed with condemned motor engine oil to scare away or trap ants and insects on entering the tyres to avoid disturbance. Feeds and water were provided throughout the study period which lasted for 16 weeks. Other management practices such as removing the leftover food, changing of water, removal of excreta were observed. The performance of the Archachatina marginata was assessed on the basis of weight gained, shell length and shell width. These parameters were measured using weighing balance and venier caliper. The Archachatina marginata treated with water melon peels showed better performance than other in terms of shell length (13.62 ± 0.31a) while the ones treated with concentrate were weightier (94.40 ± 1.07a). For circumference of the snail, the snails fed with concentrate performed better (32.36 ± 0.99), followed by 30.00 ± 0.92, 28.28 ± 0.35 and 25.32 ± 0.48 respectively. Similarly, significant weight difference(p<0.05) was noticed with the highest found in the snails treated with water melon peel (94.40 ± 1.07a) followed by Carica papaya leaves (87.00 ± 1.37b), followed by concentrate (80.00 ± 1.41c) then, Moringa oleifera leaves (74.40 ± 2.29d). It is recommended that, more natural feeds be experimented in feeding snails to test for growth and reproduction and government should sensitize and empower local farmers for snail farming.